Response Surface Methodology (RSM) on Extraction of Silica Particle from Rice Husk Ash - Azizzulrahman, Siti Nuur Shahira Shadzlin (Universiti Teknologi PETRONAS, 2021)
The development of highly reactive silica materials for the substitution of cement is important in the production of sustainable concrete. Indeed, rice husk ash (RHA) has been demonstrated to possess a large amount of silica that is vital to the production of concrete strength. In the contemporary concrete industry, use of traditional rice husk ash is still unfavourable, despite much investigation of conventional rice husk ash since the 1970s. Response surface methodology (RSM) is often used for the planning, implementation, as well as optimisation of nano silica extraction methods, and for the creation of statistical models.